Effect of pre-chamber charge temperature on engine performances and emissions of a dual chamber spark ignition engine - Chalilullah Rangkuti, (1999)
The performances, fuel economy and emissions from a dual chamber; stratified charge, spark ignition engine with heated pre-chamber charge temperature were investigated. The total hydrocarbon emissions from the engine, when tested at Leeds, proved considerably lower than in the early British Leyland study. The vaporizer system used at Leeds would probably have led to increased pre-chamber mixture temperature. It was therefore decided to investigate the effects of this mixture chamber temperature, by raising its value from 30°C used in the reference test to 45°C in a comparative test series. The good specific fuel economy and NOx emissions noted in the Leyland study were confirmed in the current work,' however the (reduced) UHC emissions found in the current tests were still excess of those expected from a conventional single chamber engine